Polyethylene oxide rubbery organic framework (ROF) membranes with enhanced CO2 permeability and CO2/CH4 selectivity - Yahia, Mohamed; Neves, Luísa A.; Giorno, Lidietta; Crespo, João; Barboiu, Mihail (Frontiers in Membrane Science and Technology, 2025)
Rubbery organic frameworks (ROFs), assembled via reversible covalent bonds under dynamic molecular control, represent a promising class of adaptive polymers for gas separation membranes. Elastomeric ROF membranes exhibit excellent mechanical stability, dynamic responsiveness, and intrinsic microporosity. Their affinity for carbon dioxide (CO2) enables both high CO2 permeability and enhanced selectivity compared to conventional glassy polymeric membranes. One effective strategy for improving CO2 separation performance is the incorporation of polyethylene oxide (PEO) units into the ROF structure. Owing to the high CO2 solubility and electrostatic interactions with PEO segments, this approach can significantly boost CO2 selectivity over other gases such as methane (CH4). In this study, a new class of PEO-based ROF membranes were developed and tailored by varying the length of PEO segments to optimize both mechanical strength and CO2/CH4 separation performance. The membranes were systematically characterized to understand the relationship between their molecular architecture, morphology, and gas transport properties. The resulting ROF membranes demonstrated CO2 permeabilities ranging from 155 to 180 barrer and CO2/CH4 selectivities between 15 and 31. Notably, a synergistic enhancement in both CO2 permeability and selectivity was observed with increasing PEO segment length. This improvement is attributed to a favorable balance of polymer chain packing, diffusivity, and CO2 affinity within the membrane matrix. These findings highlight the potential of PEO-integrated ROFs as versatile and high-performance materials for advanced gas separation applications.